Epidermal growth factor attenuates blood‐spinal cord barrier disruption via PI3K/Akt/Rac1 pathway after acute spinal cord injury. Issue 6 (15th January 2016) - Zheng, Binbin; Ye, Libing; Zhou, Yulong; Zhu, Sipin; Wang, Qingqing; Shi, Hongxue; Chen, Daqing; Wei, Xiaojie; Wang, Zhouguang; Li, Xiaokun; Xiao, Jian; Xu, Huazi; et al.
Abstract: After spinal cord injury (SCI), disruption of blood–spinal cord barrier (BSCB) elicits blood cell infiltration such as neutrophils and macrophages, contributing to permanent neurological disability. Previous studies show that epidermal growth factor (EGF) produces potent neuroprotective effects in SCI models. However, little is known that whether EGF contributes to the integrity of BSCB. The present study is performed to explore the mechanism of BSCB permeability changes which are induced by EGF treatment after SCI in rats. In this study, we demonstrate that EGF administration inhibits the disruption of BSCB permeability and improves the locomotor activity in SCI model rats. Inhibition of the PI3K/Akt pathways by a specific inhibitor, LY294002, suppresses EGF‐induced Rac1 activation as well as tight junction (TJ) and adherens junction (AJ) expression. Furthermore, the protective effect of EGF on BSCB is related to the activation of Rac1 both in vivo and in vitro . Blockade of Rac1 activation with Rac1 siRNA downregulates EGF‐induced TJ and AJ proteins expression in endothelial cells. Taken together, our results indicate that EGF treatment preserves BSCB integrity and improves functional recovery after SCI via PI3K‐Akt‐Rac1 signalling pathway.